Early double-negative thymocyte export in Trypanosoma cruzi infection is restricted by sphingosine receptors and associated with human chagas disease. - Lepletier, Ailin (2014)
Fil: Fil: Lepletier, Ailin. Laboratory on Thymus Research, Oswaldo Cruz Foundation, Rio de Janeiro, Brazil